The Effect of Liquidity, Profitability, and Solvency on Stock Prices in LQ-45 Companies Listed on The Indonesia Stock Exchange (IDX) For The Period 2020-2022 - Simbolon Joshua (Yayasan Az Zukhruf Cendikia, 2025)
Purpose – This study aims to test and analyze the relationship between liquidity, profitability, and solvency in relation to stock price Design/methodology/approach – This research was conducted using a purposive sampling. The research data includes 81 observations that focus on the Index LQ 45 with 27 samples of research during 2020-2022. The writer tested the hypothesis by using a data regression model with the SPSS tool. Findings – The results of this study found that Liquidity has a negative and insignificant effect on stock price, Profitability has a positive and significant effect on stock price, Solvency has a negative and significant effect on share price. Research limitations/implications – This research focuses on the stock price where this research study discusses the relationship of liquidity, profitability, and solvency in LQ-45 index companies